2003
DOI: 10.1200/jco.2003.02.124
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of Advanced Breast Cancer With a Heterophilic Ganglioside (NeuGcGM3) Cancer Vaccine

Abstract: NeuGcGM3/VSSP/Montanide ISA 51 is an unusual immunogenic ganglioside vaccine and also seems to be safe in this small trial. Immunologic surrogates of activity indicate that this reagent warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 23 publications
(9 reference statements)
3
71
0
1
Order By: Relevance
“…15 In the present study we demonstrated the NeuGcGM3 ganglioside expression in subcutaneous and lymph nodes metastasis of melanoma tumors. Gangliosides have been reported in plasma membrane essentially, 8 but some studies have shown the presence of gangliosides as GD3 in the cytoplasm of the mature neuronal cells.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…15 In the present study we demonstrated the NeuGcGM3 ganglioside expression in subcutaneous and lymph nodes metastasis of melanoma tumors. Gangliosides have been reported in plasma membrane essentially, 8 but some studies have shown the presence of gangliosides as GD3 in the cytoplasm of the mature neuronal cells.…”
Section: Discussionmentioning
confidence: 71%
“…In a previous clinical trial with this vaccine in advanced breast cancer patients, no vitiligo events were observed. 15 We did not find a direct association of vitiligo, the presence of anti-NeuGcGM3 ganglioside antibodies and the clinical outcome, but its relation with the vaccination process was evident, since it appeared after the administration of the first 5 vaccine doses and continued increasing after interrupting immunizations. In our case, it should be noticed that vitiligo was induced despite the fact that the vaccine formulation does not contain melanocyte antigens.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations